IMPROVEMENT OF FUNCTIONAL PROPERTIES OF BALI BEEF (M. Longissimus dorsi) THROUGH ADDITION OF LIQUID SMOKE POST MORTEM AT DIFFERENT RIGOR TIMES - Abustam, Effendi; Ali, Hikmah M (Buletin Veteriner Udayana, 2016)
In order to improve meat quality of bali cattle, application of post harvest technology is still needed to be developed. One of post mortem technologies application is addition of liquid smoke as a binder for increasing meat functional properties of bali cattle especially pH and water holding capacity. This study aimed to improve meat functional properties of bali cattle through addition of different levels of liquid smoke at different rigor times. This research utilized the muscle of Longissimus dorsi (L. dorsi) , from bali cattle aged three years. Completely randomized design in factorial pattern of 5 x 8 with five replications was used in this research. Factor 1 was  the percentage of liquid smoke of 10% concentration (0%, 0,5%, 1,0%, 1,5% and 2,0%, w/w)  and factor 2 was rigor times (1, 2, 3, 4, 5, 6, 7, and 8 hours post mortem). Parameter observed was pH and water holding capacity. The results showed that pH was decreased and water holding capacity was increased with increasing the level of liquid smoke. Furthermore, by increasing the rigor time, pH values were decreased while water holding capacity was not significantly differ.  It can be concluded that liquid smoke could increased the meat functional properties of Bali cattle especially pH and water holding capacity.
Keywords: pH; Water Holding Capacity; liquid smoke; Longissimus dorsi; bali cattle